2019
DOI: 10.1111/peps.12310
|View full text |Cite
|
Sign up to set email alerts
|

Discrete emotions linking abusive supervision to employee intention and behavior

Abstract: Drawing on appraisal theories of discrete emotions, we propose and test a model in which abusive supervision directed toward oneself and toward work unit peers (coworker abusive supervision) are interactively related to generalized feelings of shame, anger, and fear. These discrete emotions, in turn, tend to precipitate distinct responses that do not directly target the supervisor. We tested our hypotheses with a three-wave, time-lagged survey of 285 full-time workers from 55 work units. Consistent with our th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
117
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 112 publications
(185 reference statements)
6
117
0
Order By: Relevance
“…Although not conclusive, this finding suggests that shame plays a pivotal role in understanding how abusive supervision might lead to potentially constructive coping behaviours. Relatedly, with the notable exception of a recent study by Peng et al (2019), our research provides one of the first empirical examinations of shame as a salient emotional reaction to abusive supervision. Our study is theoretically different from Peng et al's (2019) research in that their investigation focused on better understanding how victims of abuse withdraw from the organization to cope with shame, rather than cope with shame through less destructive actions (e.g., exemplification).…”
Section: Theoretical Implicationsmentioning
confidence: 89%
See 3 more Smart Citations
“…Although not conclusive, this finding suggests that shame plays a pivotal role in understanding how abusive supervision might lead to potentially constructive coping behaviours. Relatedly, with the notable exception of a recent study by Peng et al (2019), our research provides one of the first empirical examinations of shame as a salient emotional reaction to abusive supervision. Our study is theoretically different from Peng et al's (2019) research in that their investigation focused on better understanding how victims of abuse withdraw from the organization to cope with shame, rather than cope with shame through less destructive actions (e.g., exemplification).…”
Section: Theoretical Implicationsmentioning
confidence: 89%
“…Relatedly, with the notable exception of a recent study by Peng et al (2019), our research provides one of the first empirical examinations of shame as a salient emotional reaction to abusive supervision. Our study is theoretically different from Peng et al's (2019) research in that their investigation focused on better understanding how victims of abuse withdraw from the organization to cope with shame, rather than cope with shame through less destructive actions (e.g., exemplification). Thus, our findings can help provide novel insights into why people do not always lash out, retaliate, or withdraw from mistreatment.…”
Section: Theoretical Implicationsmentioning
confidence: 89%
See 2 more Smart Citations
“…However, this perspective has recently been challenged by studies showing that people may also experience more selfconscious reactions such as shame (Farh & Chen, 2014;Peng et al, 2019) or guilt (Tröster & Van Quaquebeke, 2020). These studies are based on the notion that individuals' responses to abusive supervision are highly dependent on the extent to which their coworkers are being abused by the same supervisor (Duffy et al, 2006;Farh & Chen, 2014;Peng et al, 2014Peng et al, , 2019Schaubroeck et al, 2016) and that people generally prefer to be treated better than their coworkers by their leaders (Matta & Van Dyne, 2020). Accordingly, previous work has shown that people experience less shame when they experience less abuse than their peers (Peng et al, 2019).…”
mentioning
confidence: 99%